Dual labour markets: A survey - Rüdiger Wapler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1999)
Whereas the standard modern theories of unemployment were developed in the context of a single sector labour market, this paper presents a survey of how these theories can be integrated into a dual labour market setting. This approach dichotomises the labour market into two sectors, a primary with high wages and high job security, and a secondary sector with lower wages and higher labour turnover. The survey consists of three main parts. Part one applies standard labour market theories to dual labour markets. Part two extends this setup by introducing uncertain product demand. Finally, in part three, open economies are discussed. It is shown that dual labour market theory is an important contribution to understanding unemployment and therefore a useful extension of standard labour economics.
urn:nbn:de:bsz:21-opus-21149
Keywords: J21; J23; J24; J31; J41; J51; J62; J64; 330; Dual Labour Market Theory; Segmented Labour Market Theory; Unemployment; Dualer Arbeitsmarkt; Lohnstruktur; Hochqualifizierte Arbeitskräfte; Niedriglohn; Theorie